Accelerator simulation test technology and its application for single event effect evaluation in space - CHEN Qiming; GUO Gang; SUI Li; LIU Jiancheng; ZHANG Yanwen; ZHANG Fuqiang; YIN Qian; HAN Jinhua; ZHANG Zheng; SUN Haohan (He jishu, 2023)
BackgroundThe space environment contains numerous high-energy particles, and a single high-energy particle passing through a spacecraft shell bombards the electronic devices within, triggering single-particle effects such as device logic state upset and function failures, which, in turn, affect spacecraft operation reliability and mission accomplishment.PurposeNotably, ground accelerator irradiation tests provide an important and effective means for simulating space single event effects and for predicting the risks of single event effect rates for electronic devices in space applications. Generally, electronic devices can be used in spacecraft only if their resistance radiation indicators meet astronautical application requirements.MethodsSpacecraft are typically exposed to space radiation particles, primarily heavy ions and protons; therefore, single event effect simulation testing for electronic devices relies predominantly on heavy ion and proton accelerators. To address the requirements of single event effect testing, technologies such as large-area beam expansion and homogenization, high-precision beam current diagnosis, and efficient test terminals have been developed to fulfill the requirements of various test tasks.ResultsParticular focus is placed on the CIAE's (China Institute of Atomic Energy) heavy ion single event and proton single event effect simulation test techniques and the heavy ion microbeam technique for radiation sensitive area identification for electronic devices. Subsequently, the aforementioned techniques are applied to a single event effect risk evaluation for astronautical electronic devices.ConclusionsIn the future, the demand for radiation-resistant devices is expected to continue to increase in the aerospace, nuclear industry, and other radiation application fields. It is, therefore, necessary to further exploit the irradiation potential of existing domestic single event effect simulation equipment and establish new accelerator platforms with improved capacity for single event effect simulation testing.